A holistic process of R&D-based open innovation model for low-tech sectors: the green and smart furniture research project. (2016) - Papadopoulos, Ioannis; Karagouni, Glykeria; Trigkas, Marios
Although dynamic and with a reputation worldwide thanks to creativity and responsiveness, micro firms and SMEs of the furniture sector have been severely hit by the recent crises facing a significant drop in turnover. Innovation seems to be one of the most significant ways for them to differentiate and therefore survive. However, incomplete information and capability inadequacy are core weaknesses of most micro and small furniture enterprises all around Europe. Open-innovation models proposed were mainly implemented in high-tech sectors. How do they work in the low-tech furniture industry? The paper describes an effort to provide a holistic approach of implementing R&D-based open-innovation; the green and smart (GSF) project was developed by the Laboratory of Applied Marketing, Management and Economics of the Wood and Furniture Design and Technology Department (WFDT) of TEI of Thessaly Greece and endeavoured to develop a best practice of this model.